1997
DOI: 10.1002/(sici)1097-0215(19971127)73:5<707::aid-ijc16>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase-I inhibitors for human malignant glioma: Differential modulation of p53, p21, bax and bcl-2 expression and of CD95-mediated apoptosis by camptothecin and β-lapachone

Abstract: β‐lapachone and camptothecin are structurally unrelated agents thought to inhibit topoisomerase‐I activity through distinct mechanisms. We find that β‐lapachone is much more potent than camptothecin in inducing acute cytotoxic effects on human malignant glioma cells. Acute cytotoxicity induced by both drugs is apoptotic by electron microscopy, but not blocked by inhibitors of RNA or protein synthesis and not associated with changes in the expression of bcl‐2, bax, p53, p21 or GADD45 proteins. In contrast, prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 12 publications
3
37
0
Order By: Relevance
“…Several chemotherapeutic agents have also been shown to mediate cell death via the Fas/FasL pathway. [30][31][32][33] In the present study, intratumor Ad.mIL-12 gene therapy upregulated the expression of both Fas and FasL in the treated and untreated tumors (Table 2). This upregulation was specific for IL-12 as intratumor injection of Ad.b-gal had no effect ( Figure 7, Table 2).…”
Section: Discussionsupporting
confidence: 54%
“…Several chemotherapeutic agents have also been shown to mediate cell death via the Fas/FasL pathway. [30][31][32][33] In the present study, intratumor Ad.mIL-12 gene therapy upregulated the expression of both Fas and FasL in the treated and untreated tumors (Table 2). This upregulation was specific for IL-12 as intratumor injection of Ad.b-gal had no effect ( Figure 7, Table 2).…”
Section: Discussionsupporting
confidence: 54%
“…[17][18][19][20][21][22] We subsequently confirmed that growth inhibition was mediated, at least in part, by induction of apoptosis, as indicated by increased caspase 3/7 activity and intranucleosomal fragmentation. In addition, beta-lapachone-treated Y79 RB cells displayed cellular morphology characteristic of apoptosis, including chromatin condensation, nuclear fragmentation with bleb formation, and pyknotic bodies 28 (http:// www.cyto.purdue.edu/cdroms/flow/vol4/index.htm).…”
Section: Discussionmentioning
confidence: 69%
“…This agent induces potent cytotoxic effects in a wide variety of malignant human cell types, including colon, lung, prostate, breast, pancreatic, ovarian, and bone cancers, as well as leukaemia, melanoma, and malignant glioma. [17][18][19][20][21][22] Beta-lapachone appears to exert a spectrum of anticancer effects, resulting in both apoptotic 20,23,24 and necrotic 17,19 cell death. Beta-lapachone can directly inhibit DNA topoisomerases I and II, 25,26 and induce G1-and/or S-phase cell-cycle delay followed by apoptosis or necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Such a relationship was reported in p53-induced growth arrest of glioma cells. 61 Including p53 expression, additional studies are recommended to clarify the roles of Mn-SOD and ROIs in apoptosis. However, the present study revealed the importance of ROIs in apoptosis induction and suggested Mn-SOD antisense transfection as a therapeutic tool for malignancies.…”
Section: Discussionmentioning
confidence: 99%